Measurement of Dysprosium Stark Width and the Electron Impact Width Parameter. Issue 2 (February 2019) - dos Santos, Jhonatha R.; Neto, Jonas Jakutis; Rodrigues, N.; Destro, M.G.; Neri, José W.; Bueno, Patrícia; Christ, Benedito
In this work, we suggest a methodology to determine the impact parameter for neutral dysprosium emission lines from the characterization of the plasma generated by laser ablation in a sealed chamber filled with argon. The procedure is a combination of known consistent spectroscopic methods for plasma temperature determination, electron density, and species concentration. With an electron density of 3.1 × 10 18  cm –3 and temperature close to 10 4  K, we estimated the impact electron parameter for nine spectral lines of the neutral dysprosium atom. The gaps in the impact parameter data in the literature, mainly for heavy elements, stress the importance of the proposed method.